A PRISMA-compliant systematic review and network meta-analysis on the efficacy between different regimens based on Tripterygium wilfordii Hook F in patients with primary nephrotic syndrome. Issue 27 (July 2018) - Wang, Xin-bin; Dai, En-lai; Xue, Guo-zhong; Ma, Rui-ling
Abstract: Background: The present study aims to comprehensively determine the efficacy of different therapy regimens based on Tripterygium wilfordii Hook F (TwHF) for patients with primary nephrotic syndrome (PNS) using network meta-analysis method. Methods: Seven electronic databases were searched to identify randomized controlled trials (RCTs) that compared the differences between different therapy regimens based on TwHF for patients with PNS. The risk of bias in included RCTs was evaluated according to the Cochrane Handbook version 5.2.0. Network meta-analysis was performed to compare different regimens. Primary outcomes were complete remission rate and total remission rate. The secondary outcomes were hr urinary protein excretion, serum albumin, serum creatinine, and urea nitrogen. Data analysis was performed using R software. Results: A total of 40 studies involving 2846 patients with PNS were included. Compared with prednisone, the improvement in total remission rate and complete remission rate was associated with TwHF alone (odds ratio [OR] = 4.80, 95% credible intervals [CrI]: 2.20–10.00; OR = 6.30, 95% CrI: 2.90–13.00, respectively), TwHF+prednisone (OR = 2.10, 95% CrI: 1.30–3.50; OR = 2.40, 95% CrI: 1.50–3.80, respectively), TwHF+CPA (OR = 12.00, 95% CrI: 1.10–150.00; OR = 16.00, 95% CrI: 1.60–170.00, respectively), and TwHF+Cyclosporine A (OR = 28.00, 95% CrI: 3.20–250.00; OR = 35.00, 95% CrI: 4.50–270.00, respectively). Compared with TwHF alone, TwHF+prednisone showed less benefit in improving total remission rate and complete remission rate (OR = 0.44, 95% CrI: 0.21–0.91; OR = 0.38, 95% CrI: 0.19–0.77, respectively). TwHF alone, TwHF+prednisone could significantly reduce hr urinary protein excretion (MD = −0.69, 95% CrI: −1.30 to −0.14; MD = −1.00, 95% CrI: −1.90 to −0.14, respectively) and increase serum albumin (MD = 5.90, 95% CrI: 2.50–9.30; MD = 3.40, 95% CrI: 1.30–5.50, respectively) when compared to prednisone alone. TwHF alone showed significant reduction in serum creatinine when compared to CPA (MD = −19.00, 95% CrI: −37.00 to −0.56). Conclusions: TwHF alone, the addition TwHF to prednisone showed more benefit in improving total and complete remission rate, hr urinary protein excretion, serum albumin, and serum creatinine. Abstract : Supplemental Digital Content is available in the text